Dynamic modeling of performance in basketball - Malarranha, J.; Figueira, B.; Leite, N.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to identify the intra-game variation from four performance indicators that determine the outcome of basketball games, controlling for quality of opposition. All seventy-four games of the Basketball World Championship (Turkey 2010) were analyzed to calculate the performance indicators in eight 5-minute periods. A repeated measures ANOVA was performed to identify differences in time and game outcome for each performance indicator. The quality of opposition was included in the models as covariable. The effective field goal percentage (F=14.0 p <.001, Pi2=.09) influenced the game outcome throughout the game, while the offensive rebounds percentage (F=7.6 p <.05, Pi2=.05) had greater influence in the second half. The offensive (F=6.3, p <.05, Pi2=.04) and defensive (F=12.0, p <.001, Pi2=.08) ratings also influenced the outcome of the games. These results may allow coaches to have more accurate information aimed to prepare their teams for the competition.